2012
DOI: 10.1002/eco.1292
|View full text |Cite
|
Sign up to set email alerts
|

Growth, water productivity, and biomass allocation of Great Basin plants as affected by summer watering

Abstract: This study measured water‐use efficiency of wildland vegetation at the whole‐plant level during two contrasting years to better understand ecosystem responses to precipitation fluctuations in the Great Basin, USA. Biome‐representative species included grasses (Distichlis spicata, Leymus triticoides, and Sporobolus airoides), desert shrubs (Artemisia tridentata, Atriplex confertifolia, and Ericameria nauseosa), wetland/riparian plants (Glycyrrhiza lepidota, Juncus arcticus, and Salix exigua), and an exotic annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 55 publications
1
10
0
5
Order By: Relevance
“…However, within the shrubs, the C 3 shrubs were more resistant to drought than the C 4 shrubs, which showed reductions in cover, reflecting a decline in physiological performance (resulting in senescence and/or dieback). These impacts were unexpected, as C 4 plants are considered to be highly drought-resistant, and the C 4 shrubs in this study are reported to have deep roots and high water use efficiency (Hodgkinson et al 1978;Evans et al 2012). While the C 4 shrubs do not yet show widespread mortality, the data indicate that additional years of press-drought may push them beyond mortality thresholds, with a substantial impact to the ecosystem (McAuliffe and Hamerlynck 2010).…”
Section: Differential Drought Sensitivities Among Plant Functional Typesmentioning
confidence: 67%
“…However, within the shrubs, the C 3 shrubs were more resistant to drought than the C 4 shrubs, which showed reductions in cover, reflecting a decline in physiological performance (resulting in senescence and/or dieback). These impacts were unexpected, as C 4 plants are considered to be highly drought-resistant, and the C 4 shrubs in this study are reported to have deep roots and high water use efficiency (Hodgkinson et al 1978;Evans et al 2012). While the C 4 shrubs do not yet show widespread mortality, the data indicate that additional years of press-drought may push them beyond mortality thresholds, with a substantial impact to the ecosystem (McAuliffe and Hamerlynck 2010).…”
Section: Differential Drought Sensitivities Among Plant Functional Typesmentioning
confidence: 67%
“…Esta especie presenta una relación raíz parte aérea de 1.13 a 1.90, al menos en las primeras etapas de crecimiento (42) . Otros trabajos reportan para gramíneas ya desarrolladas una relación raíz parte aérea de 3 en B. gracilis y 2.5 en Hilaria mutica (45) , 4.3 en Sorghastrum nutans y 4.9 en Bouteloua curtipendula (46) y 5.5 en Sporobolus airoides, 4 en Distichlis spicata y 3 en Leymus triticoides (47) . Los valores altos representan mayor inversión de biomasa en raíces para la búsqueda de recursos (48,49) .…”
Section: Producción De Biomasaunclassified
“…Las especies nativas de zonas áridas y pastizales semiáridos que están adaptadas a suelos pobres en nutrimentos muestran una tasa de crecimiento relativo inferior a las invasoras, y la magnitud de estas diferencias se intensifica con el incremento de la disponibilidad de Sporobolus airoides, 4 in Distichlis spicata and 3 in Leymus triticoides (47) . The high values represent a higher biomass investment in roots for the search of resources (48,49) .…”
Section: Producción De Biomasaunclassified
“…The growth location affects soil moisture and nutrients, which, in turn, affects the structure, composition and aboveground biomass of the shrubs (Evans et al 2012). In most arid and semiarid regions, different water supplies level influenced aboveground biomass partitioning of shrub (Naumburg et al 2005;Mata-González et al 2012).…”
mentioning
confidence: 99%
“…In general, water in soil transported to aboveground biomass production changes with respect to different water conditions (Achten et al 2010). Shrubs with highest water requirements, such as wetland species, utilized up to 13 times more water to produce a unit of aboveground biomass than plants with the lowest requirements such as desert shrubs (Evans et al 2012). There were smaller leaves and lower specific leaf area (SLA) in water scarce environments (Padilla et al 2009).…”
mentioning
confidence: 99%